Building an Accelerated Online Graduate Program for Military Officers - Collins, Royce Ann; Kang, Haijun; Yelich Biniecki, Susan; Favor, Judy (Online Learning, 2014)
Because of the intense and unique nature of their military life, military officers face challenges that other students do not need to be concerned about when taking courses online. An institution's ability to understand these military officer students, design online programs to meet their unique learning needs, and deliver valuable online curriculum to advance their learning is instrumental to the long-term success of both the military student and the institution. Reflecting on our more than twenty years of experience teaching and mentoring military officer students, this article tells the story behind the development of an accelerated online program and shares the challenges brought along with having military officers in our online classes, including unpredictable deployment schedules, unannounced military exercises, security concerns, and military values and culture. How our faculty creatively and pedagogically addressed these challenges while still maintaining the rigor of our academic program is also discussed.